The Reliance on Vestibular Information During Standing Balance Control Decreases With Severity of Vestibular Dysfunction - van Kordelaar, Joost; Pasma, Jantsje H.; Cenciarini, Massimo; Schouten, Alfred C.; van der Kooij, Herman; Maurer, Christoph (Frontiers in Neurology, 2018)
The vestibular system is involved in gaze stabilization and standing balance control. However, it is unclear whether vestibular dysfunction affects both processes to a similar extent. Therefore, the objective of this study was to determine how the reliance on vestibular information during standing balance control is related to gaze stabilization deficits in patients with vestibular dysfunction. Eleven patients with vestibular dysfunction and twelve healthy subjects were included. Gaze stabilization deficits were established by spontaneous nystagmus examination, caloric test, rotational chair test and head impulse test. Standing balance control was assessed by measuring the body sway responses to continuous support surface rotations of 0.5 and 1.0 degrees peak-to-peak while patients had their eyes closed. A balance control model was fitted on the measured body sway responses to estimate balance control parameters, including the vestibular weight, which represents the reliance on vestibular information. Using multivariate analysis of variance (MANOVA), balance parameters were compared between patients with vestibular dysfunction and healthy subjects. Robust regression was used to investigate correlations between gaze stabilization and the vestibular weight. Our results showed that the vestibular weight was smaller in patients with vestibular dysfunction than in healthy subjects (F = 7.67, p = 0.011). The vestibular weight during 0.5 degrees peak-to-peak support surface rotations decreased with increasing spontaneous nystagmus eye velocity (ρ = -0.82, p < 0.001). In addition, the vestibular weight during 0.5 and 1.0 degrees peak-to-peak support surface rotations decreased with increasing ocular response bias during rotational chair testing (ρ = -0.72, p = 0.02 and ρ = -0.67, p = 0.04, respectively). These findings suggest that the reliance on vestibular information during standing balance control decreases with the severity of vestibular dysfunction. We conclude that particular gaze stabilization tests may be used to predict the effect of vestibular dysfunction on standing balance control.